Possibilities of use of passiflora incarnata from a phytochemical and pharmacological perspective (Research, Society and Development, 2023)
The objective of this study is “Possibilities of using Passiflora from a phytochemical and pharmacological point of view”. Carry out historical research on the use of this plant species, investigate and describe the purposes and indications for its use as pharmacotherapy, and provide guidance on the possible consequences associated with its use or misuse, taking into account the adverse and toxicological effects reported. effects. Among these properties and uses, there are anxiolytic, sedative and antispasmodic effects. Its effects were obtained through the extract of secondary metabolites found in different parts of the plant such as roots, bark, stem, leaves and flowers. The research presented here prioritizes the discovery of essential knowledge about the uses of Passiflora incarnata, and thus assumes great importance and complexity, as it is a species of Passiflora that is not cultivated in Brazil and has a broad spectrum of pharmacological activity.